Early Christian Churches and Churchyards in the North Atlantic: A Comparative Study of Iceland and Norse Greenland - Emily Patricia Paulus 2000- (2025)
An increasing number of studies and projects have been published investigating the early churches and churchyards in Iceland and Norse Greenland. It appears that these two church groups have been studied in relative isolation from one another, with only brief mentions of how they compare in construction methods and materials. Formal comparisons between different countries have not been explored. This comparative study will investigate the aspects of small churches Iceland and Greenland share and do not share in an attempt to discuss their implications as they relate to the Christian conversion. The attributes that are studied include: the location of the church in relation to the dwelling, the burial customs present, the period of use, and the construction method of the church. From studying these factors in the Skagafjörður region of Iceland and Þjóðhildarkirkja in the Eastern Settlement of Greenland, it can be said that the “blueprint” for how to organize a church and churchyard was the same in Iceland and Greenland.